KAHOOT AS LEARNING MEDIA: TEACHERS’ PERCEPTION ON VOCABULARY RETENTION IN THE FIRST GRADE OF JUNIOR HIGH SCHOOL - Ato'illah, Ato'illah; Sood, Muhammad (PENA KREATIF : JURNAL PENDIDIKAN, 2026)
Mastering vocabulary plays a key aspect of learning English. However, many students still face difficulties in remembering words they have learned for a long time. While previous studies mostly examined how Kahoot! improves students’ motivation and participation, few have discussed its role in helping students retain vocabulary. Therefore, this study aims to understand teachers’ perceptions of using Kahoot! as a learning medium to strengthen students’ vocabulary memory in the first grade of junior high school. This research used a qualitative phenomenological design involving three English teachers chosen through purposive sampling. Data were collected through structured interviews and supported by documentation. The results show that teachers view Kahoot! positively because it is enjoyable, simple to use, and helps improve students’ motivation, engagement, and word retention. Although some obstacles such as limited devices and poor internet connections appeared, teachers managed them using various creative solutions. The study suggests that Kahoot! can serve as an effective digital learning tool to make vocabulary learning more interactive, enjoyable, and memorable for students in today’s digital classroom.